Transnational Cultural Migration. Mexico-U.S. Border Experiences: A Case Study - Manzano Munguía, María Cristina; Periañez de la Rosa, Juan; Carrillo Padilla, Ana Lorena (Frontera Norte, 2022)
This paper looks at the transnational cultural experiences of a Cantonese migrant while border crossing the United States and Mexico. Specifically, we explore his experiences while residing in transnational spaces (Mexico, the United States, and Canton (Guangzhou)). Fieldwork including participant observation and qualitative data were collected through ethnographic interviews carried out during the period 2014-2016, at a Chinese food restaurant in Puebla, Mexico. Our goal is to understand the border crossing experience as a confluence of activities, which contribute to the construction of epistemologies from below and the understanding of transnationalism from a cultural approach.